Application of Nanotechnology in the Remediation of Contaminated Groundwater: A Short Review - and Himanshu Joshi, Ashutosh Agarwal* (Recent Research in Science and Technology, 2010)
Nanotechnology is an emerging science that has shown promise in humanizing various life facets ranging from medicine to industrial materials. One such application of nanotechnology is for the remediation of contaminated groundwater. Groundwater pollution is becoming a major problem not only for the developing countries like India but also for most of the developed countries of the world. In this respect the application of nanotechnology may prove a boon to the mankind by providing an advance way for groundwater treatment. The status of groundwater quality, basic idea of nanotechnology for remediation and its practical applicability, ongoing projects and future scope in India has been reviewed through this article.